Trends and social inequalities in self-reported health and activity limitations in France between 2017 and 2021: results from four nationwide representative surveys - Hana Lahbib; Laure Carcaillon-Bentata; Nathalie Beltzer; Cyrille Delpierre; Joël Coste (BMC, 2024)
Abstract Background Like other countries in Europe and around the world, France was hit by the COVID-19 pandemic in 2020, although it had also experienced several social crises since 2017. This study assessed the evolution of self-reported health and activity limitations and explored the dynamics of their socio-territorial inequalities among the French population aged 18-75 years between 2017 and 2021. Methods Self-reported health (SRH) and global activity limitation indicator (GALI) were assessed in the same way in the four last editions of the French Health Barometer surveys conducted in the general population in 2017, 2019, 2020, and 2021, with between 9,200 and 24,500 subjects interviewed depending on the year. The prevalence of good or very good SRH and GALI (any limitation) and their evolution between 2017 and 2021 were studied according to sex, age, main socioeconomic positions (SEP), and regions. Poisson regression models were used to estimate adjusted prevalence ratios and potential modification effects of sociodemographic and geographic characteristics. Results Between 2017 and 2021, SRH and GALI deteriorated in adults in France in a continuous way. Very good or good SRH decreased from 75.2% (CI95% [74.5-75.9]) of subjects in 2017 to 68.5% (CI95% [67.7-69.3]) in 2021. In parallel, GALI increased from 21.5% (CI95% [21.0-22.2) in 2017 to 25.2% (CI95% [24.5-26.0]) in 2021.The deterioration of indicators affected both sexes, all age classes (except 65-75 years), especially younger age classes (18-24 and 25-34 years), all geographical regions, and all SEP variables, with groups with a higher SEP deteriorating more than others. Negative variations exceeding 20% (8-10 percentage points on the absolute scale of indicators) were observed in several population groups from 2019 onwards. Conclusion The previously observed deterioration of the SRH and GALI continued in France between 2017 and 2021, with narrowing socio-territorial gradients of inequalities. The impact of successive social and health crises on the poor evolution of self-reported health and activity limitations warrants further investigation over time and across locations using complementary and possibly more detailed indicators.